Risk Analysis and Efficiency Islamic Banking: Evidence in Indonesia - Adi Seputra, R. Yudhistira; Azhari, Azhari; Aminul Islam, MD (IKONOMIKA, 2019)
This study aims to analyze the risk and efficiency of Bank MuamalatTbk, customers & ex-employees perceptions of the efficiency of the closure of the Branch Offices in Bojonegoro and Blora Regencies. This research is quantitative research that uses three stages of analysis. The first phase of the analysis involves risk analysis by measuring credit, operational and risk of disbursement based on the 2013-2017 Bank Muamalat Indonesia Tbk Financial Report using CAMELS financial ratios, the second stage consists of measuring the efficiency of Bank MuamalatTbk's performance using non-parametric techniques, Data Envelopment Analysis (DEA). The third stage will apply Pearson Correlation Coefficients to test the correlation between Customer Perception, Credit, Operations, and Risk of Disbursement to Efficiency. Based on results it can be concluded that the condition of Bank Muamalat Indonesia for the period 2013 - 2017 can be declared unhealthyand risky. So, it is suggested that Muamalat obtain new investors who are able to provide capital to nourish their financial performance. Keywords : Efficiency, Operational Risk, Islamic Banking, Data Envelopment Analysis.